Using the balance sheet approach in financial stability surveillance: Analyzing the Israeli economy's resilience to exchange rate risk - Haim, Yair; Levy, Roee (Journal of Financial Stability, 2010)
This paper presents a framework for analyzing an economy's resilience to exchange rate risk using the balance sheet approach (BSA), which is gaining prominence worldwide in the surveillance of financial stability. The framework is applied to Israel's economy, by using an unique and extensive dataset: a combination of new national balance sheet data and foreign currency balance sheet data. The analysis using the BSA shows that Israel's economy was highly vulnerable to a depreciation of the shekel in 1997, but from then until 2005 it became more resilient. The improvement was due mainly to the lowering of the business sector's high level of exposure to depreciation and its greater financial strength. This, together with higher capital adequacy in the banking system, made the latter more resilient to indirect damage that could be caused by depreciation. The analysis shows further that despite the heavy exposure of the economy as a whole and most sectors within it to appreciation of the shekel at the end of 2005, the economy was quite resilient to such appreciation, as the private sector and the banks suffered little direct or indirect damage through it. The analysis stresses the central, but not exclusive, role played by the banks’ resilience in the economy's financial stability, and thus also favors the continuation of the process of reducing the banks’ dominance in financing the business sector, so that their indirect exposure to financial risks will fall. The findings yielded by the BSA are highly significant, because an analysis using the traditional approach leads to very different results, viz., that in 1997 the economy was not vulnerable to changes in the exchange rate, and that in 2005 it was highly vulnerable to shekel appreciation. The conclusions in the paper support the use of the balance sheet approach as an important instrument in surveillance of financial stability, the formulation of other similar frameworks for analyzing financial risks, and the provision of more detailed data in the national balance sheet that would enable a deeper analysis of overall economic risks and the risks in the major sectors.